2014
DOI: 10.1159/000368265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Molecular and Clinical Determinants for the Involvement of Aldosterone and Its Receptors in Major Depression

Abstract: Major depression (MDE) has metabolic and neuroendocrine correlates, which point to a biological overlap between MDE and cardiovascular diseases. Whereas the hypothalamic-pituitary-adrenocortical axis has long been recognized for its involvement in depression, the focus was mostly on cortisol/corticosterone, whereas aldosterone appears to be the ‘forgotten' stress hormone. Part of the reason for this is that the receptors for aldosterone, the mineralocorticoid receptors (MR), were thought to be occupied by gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 94 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…An interesting aspect is that the sensitivity of the MR appears to be a trait rather than a state marker, as acutely depressed and recovered patients are not different (Juruena et al, 2010), which is also reflected in a reduced hippocampal MR expression in depressed patients post mortem independent of depressive state at time of death (Klok et al, 2011). These findings are in line with the suggestion that reduced peripheral MR sensitivity may lead to a counter-regulatory increase in aldosterone (Murck et al, , 2014, which affects brain function in a deleterious way. The action of aldosterone in influencing central MR-function is complex.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…An interesting aspect is that the sensitivity of the MR appears to be a trait rather than a state marker, as acutely depressed and recovered patients are not different (Juruena et al, 2010), which is also reflected in a reduced hippocampal MR expression in depressed patients post mortem independent of depressive state at time of death (Klok et al, 2011). These findings are in line with the suggestion that reduced peripheral MR sensitivity may lead to a counter-regulatory increase in aldosterone (Murck et al, , 2014, which affects brain function in a deleterious way. The action of aldosterone in influencing central MR-function is complex.…”
Section: Introductionsupporting
confidence: 70%
“…More recently a closer characterization identified the nucleus of the solitary tract (NTS), the amygdala and the paraventricular nucleus (PVN) of the hypothalamus as relevant targets (Geerling et al, 2006;Geerling and Loewy, 2009). Directly and through their connections these areas are involved in neuroendocrine regulation, salt appetite, sleep and, blood pressure regulation ( (Murck et al, 2014) for review). From a syndromal perspective these regions are involved in anxiety and depression as well as emotions, and body perception.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies have confirmed that the MR controls the neuroendocrine activation of the HPA axis not only in basal condition but also under stress context (Berardelli et al, 2013;Murck et al, 2014). In animal studies, transgenic mice lacking the MR in the forebrain displayed an altered basal and stress-induced corticosterone secretion, with especially enhanced corticosterone levels in response to restraint stress.…”
Section: Mr and Hpa-axis Activitymentioning
confidence: 96%
“…Mineralocorticoids further enhance salt appetite [2,4 ]and thus foster salt intake, as amplified in separate reviews of this special issue [20,21]. Enhanced salt intake and renal salt retention lead to extracellular volume expansion with increase of blood pressure [7,8,22].…”
Section: Effects Of Mineralocorticoidsmentioning
confidence: 99%
“…Mineralocorticoids affect neuronal function and survival [3,64,65,66,67] as amplified in a separate review of this special issue [21]. …”
Section: Effects Of Mineralocorticoidsmentioning
confidence: 99%